New way of access to public higher education: a state of knowledge on the Unified Selection System – SiSU - Ariovaldo, Thainara Cristina de Castro; Nogueira, Cláudio Marques Martins (Universidade Estadual de Campinas, 2018)
This paper presents a state of knowledge about the Unified Selection System - SiSU. The object of the study was the set of papers registered in the theses and dissertations maintained by CAPES that deal with the subject. The selection of papers (n = 16) was done based on the cadastral records and abstracts and the analysis were made with a focus on the abstracts, introductions and conclusions presented by the authors. Based on these data, it was possible to draw a panorama of contemporary Brazilian scientific production on SiSU, within the scope of postgraduate programs, identifying its main trends, such as convergent and divergent results.